Molecular understanding of polyelectrolyte binders that actively regulate ion transport in sulfur cathodes. Issue 1 (December 2017) - Li, Longjun; Pascal, Tod; Connell, Justin; Fan, Frank; Meckler, Stephen; Ma, Lin; Chiang, Yet-Ming; Prendergast, David; Helms, Brett
Abstract Polymer binders in battery electrodes may be either active or passive. This distinction depends on whether the polymer influences charge or mass transport in the electrode. Although it is desirable to understand how to tailor the macromolecular design of a polymer to play a passive or active role, design rules are still lacking, as is a framework to assess the divergence in such behaviors. Here, we reveal the molecular-level underpinnings that distinguish an active polyelectrolyte binder designed for lithium–sulfur batteries from a passive alternative. The binder, a cationic polyelectrolyte, is shown to both facilitate lithium-ion transport through its reconfigurable network of mobile anions and restrict polysulfide diffusion from mesoporous carbon hosts by anion metathesis, which we show is selective for higher oligomers. These attributes allow cells to be operated for >100 cycles with excellent rate capability using cathodes with areal sulfur loadings up to 8.1 mg cm–2 . Polymer binders in battery electrodes can affect their performance, however design rules are still lacking. Here, the authors reveal why polyelectrolyte binders outperform charge-neutral alternatives in lithium–sulfur batteries, showing how cationic polyelectrolytes can regulate ion transport selectively.